A brief review of the occurrence of Eulophinae (Hymenoptera: Eulophidae) for the Rio Grande do Sul state, with a key to genera (Caderno de Pesquisa, 2019)
The occurrence of genera and species of Eulophinae in Rio Grande do Sul is briefly analyzed, and a commented list of genera, as well as a dichotomous key, are provided. There is a new registry of species for the Brazilian and South American eulophine fauna, and for the state there is one new genus occurrence, as well as three new species.